Anticoagulation, fibrinolytic and the cytotoxic activities of sulfated hemicellulose extracted from rice straw and husk. (July 2018) - Ragab, Tamer I.M.; Amer, Hassan; Mossa, Abdel Tawab; Emam, Mahmoud; Hasaballah, A.A.; Helmy, Wafaa A.
Abstract: Rice straw and husk are one of the major agricultural wastes in Egypt, which cause problems for farmers. Hemicellulose is considered one of the major components of straw and husk lignocellulosic biomass. The new methods and techniques for hemicellulose extraction from renewable with low cost and their modification to produce a promising value-added hemicellulose derivative are important issues. Therefore, the present study aimed at extracting hemicellulose from Egyptian agriculture wastes rice straw and husk by 4% sodium hydroxide at 90 °C. The extracted hemicellulose was purified by 5% hydrogen peroxide and separated into soluble and insoluble hemicellulose in distilled water. The sulfation process of hemicellulose was done in presence of two different catalysts (N, N-Dicyclohexylcarbodiimide (DCC) and 4-Dimethylaminopyridine (DMAP)). Results showed that the sulfated soluble hemicelluloses have the highest degree of sulfation (DS) with low total carbohydrate content. The prepared sulfated hemicellulose using DCC or DMAP showed promising biological activities such as anticoagulation activity at 31.25 µg/mL and fibrinolytic activity lysis more than 80% at 2000 µg/mL compared standard (Hemoclar). These sulfated hemicellulose compounds were practically non-toxic on the VERO cells with LD50 ≥ 5000 mg /Kg. Highlights: Extracting hemicellulose from Egyptian agriculture wastes rice straw and husk. The extracted hemicellulose was purified by 5% H2 O2 and separated into soluble and insoluble hemicellulose in distilled water. The results showed a promising biological activities such as anticoagulation activity at 31.25 µg/mL and fibrinolytic activity at 2000 µg/mL.